Operationally defining sexual orientation : towards the development of a fundamental measure of adolescent sexual responsiveness variations - Heath, Lance Julian (Rhodes University, Faculty of Education, Department of Education, 2005)
Much published work has pointed to the need for the development of a sound operational definition of sexual orientation in order to enable the research in this area to progress. To contribute to this process the current research set out to develop two measures of sexual orientation and examine their psychometric properties. In order to develop relevant tools historical, conceptual and operational definitions of sexual orientation were critically examined and standard questionnaire development techniques applied. The first scale consisted of 32 items and was administered to a total of 835 adolescents, comprising three sub-groups (189 Grade 11 Scholars, 547 First Year and 99 Third Year Psychology Students). A Cronbach alpha coefficient of 0.85 was calculated indicating that this instrument had very good internal consistency reliability. Similar factors emerged in each of the sample sub-groups when factor analyses were performed suggesting that this instrument has good external and construct validities. These factors each had respectable Cronbach alpha coefficients indicating their own internal consistency. The four factors which consistently emerged were Same Sex Responsiveness, Opposite Sex Responsiveness, Previous Month's Same Sex Responsiveness and Previous Month's Opposite Sex Responsiveness. The second scale consisted of 16 items and was administered to 646 adolescents, comprising the latter two sub-groups referred to above. A Cronbach alpha coefficient of 0.82 was calculated indicating that this instrument also had very good internal consistency reliability. Once again similar factors with generally good internal consistency emerged in factor analysis suggesting that this too was a valid instrument. The factors that emerged from the second scale were Same Sex Responsiveness, Unattractive Opposite Sex Responsiveness, Attractive Opposite Sex Responsiveness and Attraction. Future developments, adjustments and applications of the instruments as well as implications for the arena of sexual orientation research are discussed. In the light of the dearth of information with regard to the sexual orientations of South African adolescents the current study also briefly explored and presented the sample's responses in terms of the dimensions of each questionnaire as well as how each emerging factor related to the demographics (education level, gender, sexual orientation self-label and age) of the sample.
Keywords: Sexual orientation; Homosexuality; Psychometrics; Teenagers--Sexual behavior